Effect of arch support foot orthosis on lower extremity loading and kinematics during the rebound - Chen, Z.-R.; Chen, Y. J.; Cheng, H.-Y.; Song, C.-Y.; Chen, Y.-H.; Peng, H.-T. (ISBS - Conference Proceedings Archive (Konstanz), 2016)
The purpose of this study was to determine whether arch support foot orthosis was capable of altering lower extremity loading and kinematics during the rebound. Nineteen female Division I basketball players participated in this study. Utilizing a repeated measures design, participants completed two rebound tasks with and without the arch support foot orthosis. Results showed that the selected arch support foot orthosis significantly decreased the peak impact force, knee internal rotation and foot inversion angle at the initial contact of the ground compared to those of the flat insole. It suggested that the use of the arch support foot orthosis can decrease the lower extremity loading and further decrease the risk of ACL injury in female basketball players.